PENGARUH VARIASI MEDIA PENDINGIN HASIL SAMBUNGAN LAS BAJA PADUAN TERHADAP NILAI KETANGGUHAN - Asfarizal; Rony Richardo (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2011)
The welding SMAW has processed in high temperature (1500oC) and variation of cooling methode will give differences of value impact. The research is weld for steel alloy with three variation lap joint (I, U, V) and three cooling media (air, sea water and oil). The analysis and solution of the research conclude that weld joint by using seam V, U and I, has the highest impact in energy and value within the air cooling media. This lap joint inclined to ductile. The lap joint in the cooling media of sea water and oil has low impact in energy and value. This lap joint inclined to brittle.